Identifying gender differences in reported occupational information from three US population-based case–control studies - Locke, Sarah J; Colt, Joanne S; Stewart, Patricia A; Armenti, Karla R; Baris, Dalsu; Blair, Aaron; Cerhan, James R; Chow, Wong-Ho; Cozen, Wendy; Davis, Faith; De Roos, Anneclaire J; Hartge, Patricia; et al. (Occupational and environmental medicine (London, England), 2014)
Objectives Growing evidence suggests that gender-blind assessment of exposure may introduce exposure misclassification, but few studies have characterised gender differences across occupations and industries. We pooled control responses to job-specific, industry-specific and exposure-specific questionnaires (modules) that asked detailed questions about work activities from three US population-based case–control studies to examine gender differences in work tasks and their frequencies. Methods We calculated the ratio of female-to-male controls that completed each module. For four job modules (assembly worker, machinist, health professional, janitor/cleaner) and for subgroups of jobs that completed those modules, we evaluated gender differences in task prevalence and frequency using χ2 and Mann–Whitney U tests, respectively. Results The 1360 female and 2245 male controls reported 6033 and 12 083 jobs, respectively. Gender differences in female:male module completion ratios were observed for 39 of 45 modules completed by ≥20 controls. Gender differences in task prevalence varied in direction and magnitude. For example, female janitors were significantly more likely to polish furniture (79% vs 44%), while male janitors were more likely to strip floors (73% vs 50%). Women usually reported more time spent on tasks than men. For example, the median hours per week spent degreasing for production workers in product manufacturing industries was 6.3 for women and 3.0 for men. Conclusions Observed gender differences may reflect actual differences in tasks performed or differences in recall, reporting or perception, all of which contribute to exposure misclassification and impact relative risk estimates. Our findings reinforce the need to capture subject-specific information on work tasks.